A Culturally Relevant Approach to Food Customs in the German Curriculum. Issue 2 (29th November 2021) - Brown, Joshua R.; Devick, Tristan; Zielinski, Connor
Abstract: To facilitate a more affirming classroom, this article highlights the implementation of culturally relevant and critical pedagogies of language learning to address issues related to social awareness in the language classroom. By appealing to cultural backgrounds of students and cultural backgrounds of diverse German‐speaking populations, students learn more about social and cultural realities in the diverse world around them. In a culturally relevant classroom, educators increase opportunities for social awareness and meaningful dialogue about social issues by making German classrooms sites of diversity learning and relevant places for critical exchange. This article shares one component of our ongoing efforts to make our entire degree program more diverse by using culturally relevant pedagogy.